solve the system by substitution -4.5 – 2y = 12.5 3.25x – y = -0.75?


In this problem, you are given a system of equations and asked to solve them. The first equation is
4.5 – 2y = 12.5
The second equation is
3.25x – y = -0.75
The third equation is
y = (-0.75)x
You are allowed to use any number of equations and variables in your solution, so long as they all work together to produce the correct answer. Can you solve the system by substitution and find the best solution?

The System Solves for x = 3.25x – y = -0.75

In this blog post, we will be discussing how to solve the system y = -. .x – y = -0.75 using substitution.

To begin, let’s take a look at the equation y = -. .x – y = -0.75 on a graph. We can see that the equation has a negative slope, meaning that as x increases, y decreases. Next, we need to find the values of x where the equation becomes true. We can do this by solving for x using substitution.

Also Read :   Find the x and y intercepts of the line 8x – 3y = 24.?

First, we will use substitution to replace y in the equation with x:

y = (-0.75)(3.25) – (-0.75)(-3.25) = 0

Next, we will use addition and subtraction to solve for x: 3.25 + (-0.75) = 3.50 and (-0.75) – 3.25 = 0

Finally, we can solve for x by dividing both sides by 2: 3.50 / 2 = 1.75 and x = 1.75


In this conclusion paragraph, the author provides a solution to the system in which they have been working. The system is one in which there are four unknowns and two equations. In order to solve for y from equation 2, the author needs to find two solutions for x from equations 1 and 3. To do this, the author multiplies both x in equation 1 by 3.25 and then subtracts that number from x in equation 2 to get a second solution for x. This second solution can be used to solve for y by substitution into equation 2.


Q: What is x in the equation y = . .x – y = -.?

A: In this equation, x represents a given unknown quantity. However, since the equation is written in terms of y and x, x can be substituted into the equation to solve for y. To do this, one must use algebraic manipulation to divide both sides of the equation by y. Doing so results in y = (-?)(x).

Also Read :   È gigantesca quella delle Tre Gole ?

Leave a Comment